Development of Contextual Learning-Based Teaching Materials in Middle School Social Studies Subjects - Mansur, Mansur; Amrin, Amrin (Yayasan Insan Mulia Bima, 2023)
The purpose of this study was to produce social studies teaching materials based on a contextual approach for class VII students of SMPN. Teaching materials contain material on economic activities related to natural resources and other potentials in the region. This research method, namely research and development (R&D) this research involved class VII students of SMPN 1 Jaya Pura. This study used questionnaires, observations, and interviews through the stages of expert trials, one-on-one evaluations, small group evaluations, and field tests. The results showed that the development of social studies teaching materials based on contextual learning could achieve very good learning outcomes.